(untitled) (Eastern Green Neurosurgery, 2020)
Even though severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (COVID-19) has been observed to mainly affect the pulmonary system, neurological (Central and Peripheral) involvements have already been reported in the literature. Also, it should be kept in mind that the patients may have COVID-19 regardless of the presence of respiratory symptoms, especially those presenting to the emergency departments (e.g. with road traffic accidents) or neurology outpatient clinics during the pandemic with neurological complaints and symptoms. A holistic approach is of great importance in protecting healthcare workers from infection as well as providing health-care to the patients and preventing late or misdiagnosis.